The adventures of the Randy Professor and Angela the Sugar Mummy: Sex in fictional serials in Ugandan popular magazines - Gysels, M.; Nyanzi, Stella; Pool, Robert (AIDS Care: Psychological and Socio-medical Aspects of AIDS/HIV, 2005)
In 1996 newspaper vendors in Ugandan towns started selling a new kind of locally produced ‘lifestyle’ magazine. On the covers there were young, scantily dressed girls and inside news articles, fictional serials, lifestyle articles, agony aunt columns, etc. The new magazines gained an enormous popularity in a short space of time. Everywhere people were seen reading them and copies became brown and tattered from use. Using content analysis, we analyse the fictional serials which appeared in three of these magazines. We focus on these because they were the most sexually explicit type of content and, from a public health perspective, the most relevant with regard to HIV prevention. The stories were presented as simple entertainment, depicting the adventures of stereotypical characters. They provided people with explicit and unrestricted sexual fantasy which was, at the same time, devoid of any real risk. Although they could be interpreted as providing a discourse which challenged the main messages of HIV-prevention campaigns (sex is good for you, have as much of it as possible, and don’t let condoms spoil the enjoyment), they also suggest that behaviour change may be more popular if sex and sexual health are not separated from sexual pleasure, and safe sex is promoted from a positive perspective (emphasis on sexual enjoyment) rather than a negative one (prevention of disease). The popularity of the magazines underscores the importance of entertainment value when discussing sex, and suggests alternative possibilities for disseminating health messages. Illustrated popular magazines such as those discussed here could be suitable as intervention, though they would need some adaptation to counter gender stereotypes and sexual violence.
Keywords: Sugar Mummy; Sex in fictional serials; adventures